Potential of Artificial Intelligence to Generate Health Research Reports of Decayed, Missed and Restored Teeth - Costa, Eliana Dantas; Carneiro, José Andery; Guerra Zancan, Breno Augusto; Gaêta-Araujo, Hugo; Oliveira-Santos, Christiano; Macedo, Alessandra Alaniz; Tirapelli, Camila (Odovtos - International Journal of Dental Sciences, 2024)
This study aims to indicate the potential of artificial intelligence (AI) in epidemiological reports of decayed, missed and restored teeth. As a proof of concept our study model used panoramic x-ray images and an AI algorithm for tooth numbering, detection of the caries and restorations with accuracy over 80% for such diagnostic tasks. The output came as the number of decayed, missed and restored teeth according to patient´s age and the DMFT index (number of decayed, missing, and filled teeth) which varied from 3.6 (up to 20 years old) to 20.4 (+60 years old). Thus, it is suggested that AI is a promising method to automate health data collection through the analysis of x-rays.